2014
DOI: 10.1002/hed.23514
|View full text |Cite
|
Sign up to set email alerts
|

p16 status, pathologic and clinical characteristics, biomolecular signature, and long‐term outcomes in head and neck squamous cell carcinomas of unknown primary

Abstract: Background To report associations between p16 status, clinicopathologic characteristics, and outcomes for unknown primary head and neck squamous cell carcinoma (SCCUPS). Methods Specimens of SCCUPS were re-analyzed. HPV status was determined by p16 stain. A tissue microarray (TMA) was constructed to evaluate biomarkers potentially prognostic in HNSCC. Results A majority of the population (n = 26, 74%) was p16+. Prognostic factors benefitting survival were p16+ status (p < 0.0001), absence of macroscopic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 33 publications
10
100
1
2
Order By: Relevance
“…In our cohort the prevalence of HPV-positivity in patients with CUP was with 30% clearly lower compared to 70% in patients with a detected PT but in line with the literature (18-40%) [54][55][56][57]. Only Keller et al [58] reported with 74% (26/39) on a higher prevalence of p16 expression in lymph node metastases in patients with CUP. Besides the epidemiologic impact of HPV-positivity in OPSCC the HPV-status of a tumor also plays an important prognostic role.…”
Section: Discussionsupporting
confidence: 72%
“…In our cohort the prevalence of HPV-positivity in patients with CUP was with 30% clearly lower compared to 70% in patients with a detected PT but in line with the literature (18-40%) [54][55][56][57]. Only Keller et al [58] reported with 74% (26/39) on a higher prevalence of p16 expression in lymph node metastases in patients with CUP. Besides the epidemiologic impact of HPV-positivity in OPSCC the HPV-status of a tumor also plays an important prognostic role.…”
Section: Discussionsupporting
confidence: 72%
“…Finally, similar to oropharyngeal cancers, recent data have implicated human-papillomavirus (HPV) association as a major prognostic factor for disease-free and overall survival in patients with HNCUP. [28][29][30][31] Irradiating the oropharynx alone may be sufficient for a patient with a HPV-associated cancer and no involved lymph nodes below level II. However, any suspicion of nasopharyngeal primary tumors warrants coverage of the nasopharynx, as recent data have associated HPV-positive nasopharyngeal carcinomas with a significantly worse prognosis compared with their HPV-negative counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published in 2007 regarding non-oropharyngeal HNSCC shows congruent results [68]. However, most of the published literature agrees that HPV/p16 is a positive prognostic indicator for HNCUP [69,70].…”
Section: Molecular Studiesmentioning
confidence: 98%
“…The current paradigm for the indications for postoperative chemo-irradiation (R1, pN3b) originates from the pre-HPV-stratification era [104,105]. Keller et al [70] have conducted an analysis of clinicopathological data, including p16 and extracapsular extension (ECE), in HNCUP and could demonstrate a very similar prognosis in patients with or without ECE, even without chemotherapy, but the patient numbers in this analysis where very limited and so no safe conclusions can be drawn. A treatment-deescalation for HPV/p16 nonsmokers could be imaginable, either through omitting chemotherapy or even by using chemotherapy in order to reduce RT-dose, following the paradigm of current HNSCC trials [102].…”
Section: Which Volumes Should Be Irradiated?mentioning
confidence: 99%